Genome-Wide Association Study of Cadmium Accumulation at the Seedling Stage in Rapeseed (Brassica napus L.) - Chen, Lunlin; Wan, Heping; Qian, Jiali; Guo, Jianbin; Sun, Chengming; Wen, Jing; Yi, Bin; Ma, Chaozhi; Tu, Jinxing; Song, Laiqiang; Fu, Tingdong; Shen, Jinxiong (Frontiers in Plant Science, 2018)
Cadmium (Cd) is a potentially toxic heavy metal. Rapeseed (Brassica napus L.) is cultivated as a vegetable and for oil production. It may also be a Cd hyperaccumulator, but there is little information on this trait in rapeseed. We evaluated Cd accumulation in different rapeseed accessions and conducted a genome-wide association study (GWAS) to identify Cd accumulation-related quantitative trait loci (QTL). A total of 419 B. napus cultivars and inbred lines were genotyped with a Brassica 60K Illumina Infinium SNP array. Wide genotypic variations in Cd concentration and translocation were found. Twenty-five QTL integrated with 98 single-nucleotide polymorphisms (SNPs) distributed across 15 chromosomes were associated with Cd accumulation traits. They explained 3.49–7.57% of the phenotypic variation observed. Thirty-two candidate genes were identified in these genomic regions and they were 0.33–497.97 kb away from the SNPs. We compared the loci of the significant SNPs we found with those in the Arabidopsis thaliana genome. We found orthologs to those genes in Brassica including NRAMP6, IRT1, CAD1, PCS2, and others. 4 candidate genes were verified by qRT-PCR whitch increasing the express level in roots significantly after exposed to Cd. Our results may facilitate the study of genetic Cd accumulation control and the cloning of candidate Cd accumulation genes for breeding low-Cd or hyperaccumulator rapeseed cultivars.